Immunodeficiency, centromeric instability and facial anomalies syndrome type 1-homozygous c.2301+2_2301+24del mutation in DNMT3B gene - Haleema, Nuwera; Anjum, Bahadur; Begum, Salma (International Journal of Contemporary Pediatrics, 2024)
Immunodeficiency with centromeric instability and facial anomalies (ICF) syndrome is a primary immunodeficiency, predominantly characterized by agammaglobulinemia or hypoimmunoglobulinemia, centromere ICF. We present a case of a 3-month-old male infant was an inpatient in a district general hospital in East London with bronchiolitis requiring intravenous antibiotics and high flow oxygen therapy. He was discharged on day 12 of admission as clinically improving, however, he represented soon after discharge with worsening respiratory compromise. Intubation and transfer to a tertiary paediatric intensive care unit were needed. Subsequent investigations depicted neutropenia, anaemia and hypo-gamma-globulinaemia. A diagnosis of ICFS syndrome type 1 with mutation in DNMT3B gene was made.